Therapeutic implications of cellular and molecular biology of cancer stem cells in melanoma. Issue 1 (December 2017) - Kumar, Dhiraj; Gorain, Mahadeo; Kundu, Gautam; Kundu, Gopal
Abstract Melanoma is a form of cancer that initiates in melanocytes. Melanoma has multiple phenotypically distinct subpopulation of cells, some of them have embryonic like plasticity which are involved in self-renewal, tumor initiation, metastasis and progression and provide reservoir of therapeutically resistant cells. Cancer stem cells (CSCs) can be identified and characterized based on various unique cell surface and intracellular markers. CSCs exhibit different molecular pattern with respect to non-CSCs. They maintain their stemness and chemoresistant features through specific signaling cascades. CSCs are weak in immunogenicity and act as immunosupressor in the host system. Melanoma treatment becomes difficult and survival is greatly reduced when the patient develop metastasis. Standard conventional oncology treatments such as chemotherapy, radiotherapy and surgical resection are only responsible for shrinking the bulk of the tumor mass and tumor tends to relapse. Thus, targeting CSCs and their microenvironment niche addresses the alternative of traditional cancer therapy. Combined use of CSCs targeted and traditional therapies may kill the bulk tumor and CSCs and offer a promising therapeutic strategy for the management of melanoma.